The Desire of the Museum. (New York : Whitney Museum of American Art, 1989)
Artschwager, Richard ; Bickerton, Ashley ; dion, Mark ; Simon, Jason ; Duchamp, Marcel ; Fraser, Andrea ; Lawler, Louise ; Guerrilla Girls ; Haacke, Hans ; Kolbowski, Silvia ; Kosuth, Joseph ; Kruger, Barbara ; Larner, Liz ; Lawler, Louise ; etc.
The Desire of the Museum, Whitney Museum of American Art, New York, July 12 - September 12, 1989
boek